Κόποις» ή «copies»; Μαθητικές/ φοιτητικές αφηγήσεις και κοινωνική ποιητική - Benincasa, Luciana (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
Adopting a voluntaristic approach, this paper aims to highlight the creativity of social actors. My objectives are (a) to examine examples of the dominant meritocratic narrative in students’ interview discourse and (b) to present an example of the way in this same narrative is challenged by other student narratives. I use two types of data from student culture: (a) excerpts from newspaper interviews with students, referred to as the “first of the first”, who were admitted with the highest marks to very prestigious university departments and (b) a well-known student saying about achievement. The students’ interview discourse resounds with the ideology of effort, described as the road to success and endorsed by educational and political authorities alike. The saying in question, on the other hand, proposes a very different narrative, according to which success is the result of cheating. More than being just different, this alternative narrative openly questions and even ridicules official narratives and the ideology that backs them. This is discussed as an aspect of “social poetics” (Herzfeld).